Biodegradation of palm kernel cake by cellulolytic and hemicellulolytic bacterial cultures through solid state fermentation - Alshelmani, Mohamed Idris; Loh, Teck Chwen; Foo, Hooi Ling; Lau, Wei Hong; Sazili, Awis Qurni (Hindawi Publishing Corporation, 2014)
Four cellulolytic and hemicellulolytic bacterial cultures were purchased from the Leibniz Institute DSMZ-German Collection of Microorganisms and Cell Culture (DSMZ) and the American Type Culture Collection (ATCC). Two experiments were conducted; the objective of the first experiment was to determine the optimum time period required for solid state fermentation (SSF) of palm kernel cake (PKC), whereas the objective of the second experiment was to investigate the effect of combinations of these cellulolytic and hemicellulolytic bacteria on the nutritive quality of the PKC. In the first experiment, the SSF was lasted for 12 days with inoculum size of 10% (v/w) on different PKC to moisture ratios. In the second experiment, fifteen combinations were created among the four microbes with one untreated PKC as a control. The SSF lasted for 9 days, and the samples were autoclaved, dried, and analyzed for proximate analysis. Results showed that bacterial cultures produced high enzymes activities at the 4th day of SSF, whereas their abilities to produce enzymes tended to be decreased to reach zero at the 8th day of SSF. Findings in the second experiment showed that hemicellulose and cellulose was significantly (P < 0.05) decreased, whereas the amount of reducing sugars were significantly (P < 0.05) increased in the fermented PKC (FPKC) compared with untreated PKC.